2018
DOI: 10.1039/c8dt02250j
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks-derived core–shell Fe3O4/Fe3N@graphite carbon nanocomposites as excellent non-precious metal electrocatalyst for oxygen reduction

Abstract: Metal–organic frameworks (MOFs), as precursors for synthesizing new carbon materials, hold promise for applications in the oxygen reduction reaction (ORR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…The former is among the highest reported value of the ORR activity in alkaline medium for PGM-free catalysts. [42][43][44][45][46] Its lower initial activity in acidic than in alkaline electrolyte can mostly be assigned to a fast protonation of highly-basic nitrogen groups followed by anion-adsorption on positively-charged [NH] + groups, which had been previously shown, on other NH 3 -pyrolyzed Fe-N-C catalysts, to divide the activity by a factor 5 to 10. 27,45,47 High initial activity of NH 3 -pyrolyzed Fe-N-C catalysts in acidic liquid-electrolyte could previously be achieved only with high catalyst loading and optimized Nafion/catalyst ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The former is among the highest reported value of the ORR activity in alkaline medium for PGM-free catalysts. [42][43][44][45][46] Its lower initial activity in acidic than in alkaline electrolyte can mostly be assigned to a fast protonation of highly-basic nitrogen groups followed by anion-adsorption on positively-charged [NH] + groups, which had been previously shown, on other NH 3 -pyrolyzed Fe-N-C catalysts, to divide the activity by a factor 5 to 10. 27,45,47 High initial activity of NH 3 -pyrolyzed Fe-N-C catalysts in acidic liquid-electrolyte could previously be achieved only with high catalyst loading and optimized Nafion/catalyst ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are a series of adjustable organic-inorganic hybrid materials with adjustable structures [37,38]. In short, metal ions are uniformly dispersed at the atomic level in the MOFs precursor, and the presence of organic ligands in the MOFs enables them to be calcined into various carbon materials without introducing an external carbon source [39]. As a general precursor for the preparation of TMPs, MOFs compounds have been extensively studied by reason of their large specific surface area, high porosity, and structural coordination [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst featured a half-wave potential (0.820 V) similar to that of Pt/C (0.865 V) but presented a higher limiting current density, which was probably due to the enhanced diffusion of species in the hierarchical pore structure. The MOF-based catalyst proposed by Su et al [ 128 ] showed the best performance in alkaline media, featuring a half-wave potential (0.916 V) that was above that of Pt/C (0.885 V). The material was characterized by a high BET surface area (918.4 m 2 g −1 ) and high porosity due to a cross-linked carbonaceous structure.…”
Section: Discussionmentioning
confidence: 99%
“…Another MOF-based catalyst prepared using polyaniline (PANI) as a carbon and nitrogen source was reported by Su et al [ 128 ]. First, MIL-101(Fe) nanoparticles were synthesized using a microwave-assisted method and mixed with freshly prepared PANI.…”
Section: Mof-based Orr Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation